Belarusian software for nuclear knowledge management - S. N. Sytova (Ядерна фізика та енергетика)
A review of Belarusian software developed for nuclear knowledge management is presented. It includes the system eLab-Control that is an information system for monitoring the nuclear and radiation safety of the national nuclear regulatory body as well as content management system eLab-Science and the Belarusian educational portal of nuclear knowledge BelNET developed on its base. All the software is based on free software: Debian GNU/Linux, Web-server Apache, the Firebird database server, PHP application server. The system runs under Windows and Linux. The work is carried out through the Internet in multiplayer mode, with the division of access rights by way of widespread browsers. Portal of nuclear knowledge BelNET https://belnet.bsu.by/ is considered from the point of nuclear knowledge management.